Attitude towards COVID-19 Vaccine among Pregnant Women: Sikap terhadap Vaksinasi COVID-19 di kalangan Ibu Hamil - Kasturi V. Donimath; Divyashree Bhat; Venkatesha K. Vasudevamurthy; Rashmi S Desai; Ashwini H. Rmaswamy (Indonesian Journal of Obstetrics and Gynecology, 2023)
Objective: To assess the perceptions and intentions of pregnant women regarding COVID-19 vaccination and to explore the reasons for vaccine hesitancy as well as acceptance. Methods: This prospective cross-sectional study was conducted in tertiary care hospital in Karnataka. Around 811 pregnant women attending the antenatal clinic were recruited into the study. Data were collected using a face-to-face, anonymous questionnaire written in local language.Results: Eighty six point two percent participants were aged 20 to 30 years and 64.6% had completed their schooling. 94.3% of them were homemakers and 58 % of the participants were in their third trimester. 65.5% of study group members lived in a COVID-supportive environment. Participants with COVID-19 vaccination awareness accounted for 87.4% and 65.4% were willing to receive the same whole heartedly. Our study found that 65.4% of participants were willing to receive covid-19 vaccine. The reasons for refusal were Lack of sufficient information regarding the vaccine, may be harmful to foetus and mother and lack of data proving its quality and efficiency.Conclusion: Pregnant women in the North Karnataka region were highly receptive to COVID-19 immunization. Although a high level of awareness was apparent, the lack of data and fear of side effects were two major concerns for refusal. Confidence in the government and the availability of free vaccines for all have demonstrated a massive impact on vaccination. Keywords: antenatal, covid-19, pregnancy, vaccination.AbstrakTujuan: Menilai persepsi dan keinginan perempuan hamil terkait vaksin COVID-19 dan alasan terkait penerimaan dan juga keraguan terhadap vaksin.Metode: Penelitian ini merupakan penelitian potong lintang dengan pendekatan prospektif yang dilakukan di Rumah Sakit Karnataka. Perempuan hamil sebanyak 811 menjadi subjek penelitian. Data dikumpulkan menggunakan kuesioner yang dituliskan dalam Bahasa lokal dan pengumpulan data dilakukan secara tatap muka. Hasil: Sebanyak 86,2 % sampel penelitian berusia 20 hingga 30 tahun dan 64,6% telah lulus sekolah. Sebanyak 94,3% sampel adalah ibu rumah tangga dan 58% dari sampel dengan usia kehamilan pada trimester ketiga. Sebanyak 65,5% grup tinggal pada kondisi. Sebanyak 87,4% sampel sadar akan keutamaan vaksin dan 65,4% bersedia mendapatkan vaksin. Alasan penolakan terhadap vaksin adalah kurangnya pengetahun mengenai vaksin dan ketakutan akan efek sampingnya.Kesimpulan: Perempuan hamil di Karnatakan Utara terbuka terhadap imunisasi COVID-19. Disamping tingginya angka kesadaran akan imunisasi COVID-19, penolakan umumnya didominasi akibat kurangnya pengetahuan dan ketakutan akan efek samping. Keyakinan pada pemerintah dan ketersediaan vaksin secara gratis sangat berpengaruh pada vaksinasi.Kata kunci: antenatal. covid-19, kehamilan, vaksinasi.